Pengaruh Pupuk NPK Pelet dari Kotoran Ayam terhadap Pertumbuhan dan Hasil Tanaman Kedelai (Glycine max l.) di Tanah Regosol - Murselindo, Anggi Aprian (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2014)
The research was conducted to determine the appropiate dose of NPK chicken manure pellets to increase the growth and yield of soybean crops in the regosol soil. The method of this research was used experimental research with single factor which is arranged in Completaly Randomized Design (CRD). The treatments were 50 kg/h Ure + SP-36 150 g/h + KCI 100 kg/h (KO), NPK of chicken manure pellets 500 kg/h (K1), NPK of chiken manure pellets 1tons/h (K2), NPK of chicken manure pellets 1.5 ton/h (K3) NPK of chicken manure pellets 2 tons/h (K4), NPK chicken manure pellets of 2,5 tons/h (K5). The results of this research showed that NPK fertilization with chicken manure pellets can replace urea fertilizer recommendation simultaneously Multitusting as much as 80% SP36 53,3% and KC160% in soybean cultivation on Regosol soil and a dose of 500 kg/h NPK chicken manure pellets was more efective to growth and yield of soybean.